2023
DOI: 10.1186/s13148-023-01529-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of FDA-approved IDH inhibitors in the treatment of IDH mutated acute myeloid leukemia: a systematic review and meta-analysis

Abstract: Objective To systematically evaluate the efficacy and safety of FDA-approved isocitrate dehydrogenase (IDH) inhibitors in the treatment of IDH-mutated acute myeloid leukemia (AML). Methods We used R software to conduct a meta-analysis of prospective clinical trials of IDH inhibitors in the treatment of IDH-mutated AML published in PubMed, Embase, Clinical Trials, Cochrane Library and Web of Science from inception to November 15th, 2022. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…IDH1 and IDH2 mutations are associated with the differentiated FAB-M2 phenotype [ 104 , 216 ]. Differentiation syndrome is seen in 15–20% of patients during IDH inhibitory treatment; the risk factors for its development are high leukemia cell burden and concomitant TET2 and SRS2 mutations, and the syndrome is characterized by leukocytosis with increased neutrophil and monocyte levels, but the syndrome is not associated with improved outcome [ 217 , 218 , 219 ]. Furthermore, enasidenib is an IDH2 mutant inhibitor that can increase the sensitivity to venetoclax; this sensitizing effect was observed both in vitro and in human AML xenograft models and seemed to depend on whether the leukemic cells differentiated (i.e., decreased c-kit/CD117 and increased granulocytic marker GR-1) in response to the enasidenib treatment [ 220 ].…”
Section: Aml Cell Differentiation and Targeted Therapies: Effect Of D...mentioning
confidence: 99%
“…IDH1 and IDH2 mutations are associated with the differentiated FAB-M2 phenotype [ 104 , 216 ]. Differentiation syndrome is seen in 15–20% of patients during IDH inhibitory treatment; the risk factors for its development are high leukemia cell burden and concomitant TET2 and SRS2 mutations, and the syndrome is characterized by leukocytosis with increased neutrophil and monocyte levels, but the syndrome is not associated with improved outcome [ 217 , 218 , 219 ]. Furthermore, enasidenib is an IDH2 mutant inhibitor that can increase the sensitivity to venetoclax; this sensitizing effect was observed both in vitro and in human AML xenograft models and seemed to depend on whether the leukemic cells differentiated (i.e., decreased c-kit/CD117 and increased granulocytic marker GR-1) in response to the enasidenib treatment [ 220 ].…”
Section: Aml Cell Differentiation and Targeted Therapies: Effect Of D...mentioning
confidence: 99%
“…It has been found that IDH inhibitors. Enasidenib and ivosidenib have been approved for the treatment of BC ( Chen et al, 2023 ). In addition, Dichloroacetate, a PDK inhibitor, contributes to the increase of PDH activity, and has been reported to have significant antimicrobial activity against NSCLC and metastatic breast cancer.…”
Section: Targeting Glucose Metabolismmentioning
confidence: 99%
“…Epigenetics is a highly complicated mechanism and phenomenal advancements have been made in the comprehensive characterization of methylation-associated machinery [89][90][91][92][93][94][95][96]. AhR has been shown to utilize different mechanisms to regulate epigenetics.…”
Section: Epigenetics Related To Ahr-mediated Downstream Signalingmentioning
confidence: 99%